Dupilumab-Associated Ocular Surface Disease: Clinical Characteristics, Treatment, and Follow-Up. Issue 5 (May 2021) - Bohner, Austin; Topham, Christina; Strunck, Jennifer; Haynes, Dylan; Brazil, Molly; Clements, John; Simpson, Eric; Chamberlain, Winston
Abstract : Purpose: A consecutive case series of patients with dupilumab-associated ocular surface disease (DAOSD) that describes common ocular symptoms and signs, proposes a symptom disease severity grading system, and describes treatment strategies of DAOSD patients was evaluated. Methods: A retrospective chart review of patients with concomitant dupilumab-treated atopic dermatitis and DAOSD with ophthalmic evaluation between January 2014 and May 2019 was conducted. Results: Twenty-nine patients (mean age 46 years, M/F: 12/17) with 57 ophthalmic exams were identified. The most common ocular symptoms included irritation/pain (n = 28, 97%), redness (n = 24, 83%), pruritus (n = 18, 62%), discharge (n = 18, 62%), and light sensitivity (n = 6, 21%). The most frequent signs included conjunctival injection (n = 18, 62%), superficial punctate keratitis (n = 16, 55%), and papillary reaction (n = 8, 28%). Topical corticosteroids (TCS) (n = 23, 79%), tacrolimus (n = 6, 21%), and artificial tears (n = 7, 24%) were the most commonly used therapies. Of those with follow-up documentation (n = 21), 20 were noted to have partial or complete response with TCS based on symptoms and reduction of signs. Using our proposed symptom-based grading scale, scaled 1 to 5 based on the presence of common symptoms listed above, 66% (n = 19) requiring topical immunomodulating therapy were found in the 'severe' group (≥3 symptoms) and 17% (n = 5) were found in the 'mild' group (⩽2 symptoms). Conclusions: This study provides insight into the commonly presenting ocular signs and symptoms associated with DAOSD and highlights the efficacy of TCS and other immunomodulators in improving symptoms associated with DAOSD. Based on our findings, we propose a symptom-based grading system that can guide nonophthalmic physicians regarding ophthalmology consult.